Versatile and active THz wave polarization modulators using metamaterial/graphene resonators - Zaman, Abdullah M.; Lu, Yuezhen; Almond, Nikita W.; Burton, Oliver J.; Alexander-Webber, Jack; Hofmann, Stephan; Mitchell, Thomas; Griffiths, Jonathan D. P.; Beere, Harvey E.; Ritchie, David A.; Degl’Innocenti, Riccardo (Frontiers in Nanotechnology, 2023)
Active modification of the polarization state is a key feature for the next-generation of wireless communications, sensing, and imaging in the THz band. The polarization modulation performance of an integrated metamaterial/graphene device is investigated via a modified THz time domain spectroscopic system. Graphene’s Fermi level is modified through electrostatic gating, thus modifying the device’s overall optical response. Active tuning of ellipticity by >0.3 is reported at the resonant frequency of 0.80 THz. The optical activity of transmitted THz radiations is continuously modified by >21.5o at 0.71 THz. By carefully selecting the transmitted frequency with the relative angle between the incoming linear polarization and the device’s symmetry axis, active circular dichroism and optical activity are almost independently exploited. Finally, this all-electronically tuneable versatile polarization device can be used in all applications requiring an ultrafast modulation such as polarization spectroscopy, imaging, and THz wireless generation.